Critical Analysis of Tax Audit Process: Evaluative Study at DGT Regional Office of South Jakarta II - Khoerul Arif; Arifin Rosid (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
A tax audit constitutes a primary business process within the framework of the DGT. While the efficacy of tax audits in augmenting tax revenue is evident, their concomitant effect of escalating tax disputes in the tax court is equally salient. The objective of this study is to evaluate the tax audit process at DGT. The evaluation employs criteria from the Organization for Economic Co-Operation and Development (OECD), including accuracy, efficiency, objectivity, transparency, fairness, completeness, defensibility, and consistency. The research method employed is qualitative, with a case study approach. The data were collected through surveys, document analysis, and interviews. The research focuses on the DGT Regional Office of South Jakarta II. The research encompasses a specific audit type, namely a field audit conducted by functional tax auditors, spanning the period from 2021 to 2023. The results demonstrated that a portion of the tax audit process has been conducted in alignment with OECD criteria. However, there is room for improvement in audit processes, particularly regarding the identification of taxpayer non-compliance. Furthermore, the audit process can be conducted in accordance with the criteria if the taxpayer is cooperative.